Demonstration of Circulating Antibodies of Mycobacterium avium Subspecies paratuberculosis in Cattle of Rupandehi District, Nepal - Sharma, M. L.; Prajapati, M.; Panth, Y. (Nepalese Veterinary Journal, 2019)
Paratuberculosis, caused by Mycobacterium avium subspp. paratuberculosis, is a chronic intestinal infection of global importance in mainly domestic and wild ruminants. The main objective of the study was to find out the seroprevalence of Paratuberculosis in cattle of Rupandehi district. The research was conducted from October 2016 to December 2016. A total of 184 blood samples were collected from Jugular vein of cattle and tested by Enzyme Linked Immunosorbent Assay (ELISA). The Paratuberculosis Indirect Screening Test Kit was developed by ID. Vet, France. Cattle with history of chronic diarrhoea and emaciation were taken as study population along with other cattle in close association with them. Overall seroprevalence in Rupandehi district was found to be 4.89%. No significant relation of paratuberculosis was found with age, breed, parity, body condition score and location. Higher prevalence was found in cattle of older age and low body condition score. The result of this study reports the presence of bovine paratuberculosis in cattle of Rupandehi district.